Exploring Trends in Physics Practicum: A Literature Review and Bibliometric Analysis - Herman; Kaniawati, Ida; Setiawan, Agus; Rusdiana, Dadi (Pendidikan Fisika UIN Alauddin Makassar, 2025)
This study aims to conduct a literature review on physics practicum using the Systematic Literature Review (SLR) method and bibliometric analysis through visual mapping with the VOSviewer software. The focus of this research is on articles published between 2020 and 2025, with the keyword